2012
DOI: 10.1016/j.scitotenv.2012.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Stream ecosystem integrity is impaired by logging and shifting agriculture in a global megadiversity center (Sarawak, Borneo)

Abstract: ► We compare ecosystem integrity of pristine vs. logged vs. farmed streams in Borneo. ► We use both functional (leaf breakdown) and structural indicators (associated fauna). ► Both practices alter ecosystem integrity, but the impacts of logging are more severe. ► Mechanized logging affects both the structure and function of stream ecosystems. ► Slash and burn clearing for shifting agriculture affects structure more than function. Keywords: Ecological integrity Structural and functional indicators Decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
0
19
1
1
Order By: Relevance
“…Some tropical invertebrates clearly differ from temperate species in terms of pollution tolerance. For example, Ephemeroptera and Chironomidae in the region (Yule et al 2010, Jinggut et al 2012) seem to be more pollution tolerant than their temperate counterparts, in part because they are adapted to elevated temperatures, and are small with shorter life cycles (Marchant 1982, Schowalter 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some tropical invertebrates clearly differ from temperate species in terms of pollution tolerance. For example, Ephemeroptera and Chironomidae in the region (Yule et al 2010, Jinggut et al 2012) seem to be more pollution tolerant than their temperate counterparts, in part because they are adapted to elevated temperatures, and are small with shorter life cycles (Marchant 1982, Schowalter 2006.…”
Section: Discussionmentioning
confidence: 99%
“…However, Del Arco et al (2012) reported that temperate urban streams in Portugal exhibited slower litter decomposition than forested streams. Jinggut et al (2012) reported a gradient of decomposition rates in Bornean streams flowing through undisturbed, farmed, and logged forests, and attributed slower decomposition rates to high rates of sedimentation in the logged stream and increased microbe-mediated decomposition consequent to external nutrient inputs from agricultural practices. Chadwick et al (2006) reported that high levels of toxic compounds can impede microbial activity and retard litter breakdown, but such conditions would be more likely to arise from industrial pollution or mining activities than the lower levels of pollutants in household and stormwater discharge in Ampang River.…”
Section: Discussionmentioning
confidence: 99%
“…In many parts of the world, landuse change, particularly loss of riparian vegetation, has resulted in loss of diversity and major shifts in the structural and functional organization of macroinvertebrates in streams (Allan 2004, Benstead and Pringle 2004, Jinggut et al 2012). Loss of riparian forests increases stream temperatures through loss of shade (Baxter et al 2005), reduces inputs of leaf litter, and affects the relative differences between wet and dry seasons (Wantzen et al 2008).…”
mentioning
confidence: 99%
“…Mientras que un mayor grado de intervención de las zonas ribereñas en las microcuencas Llaviuco y Matadero pudo afectar significativamente estas comunidades, lo que no permitió diferenciar la actividad de los invertebrados y la de los microorganismos durante el proceso de descomposición. El cociente K g /K f ha sido utilizado para evaluar la importancia de los invertebradores fragmentadores en ríos tropicales (Jinggut, Yule, & Boyero, 2012;Masese et al, 2014;Casotti et al, 2015). De acuerdo a Boyero et al (2015) muchos sitios tropicales que tienen K g /K f >fragmentadores en la descomposición de la hojarasca es importante.…”
Section: Discussionunclassified